HAPUSNYA PERIKATAN UTANG PIUTANG KARENA PERCAMPURAN UTANG MELALUI PERKAWINAN DALAM KITAB UNDANG-UNDANG HUKUM PERDATA DAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 TENTANG PERKAWINAN - Abd. Djalil Ghaffar (Lembaga Pengembangan Kinerja Dosen, 2023)
One of the reasons for the cancellation of the agreement is the occurrence of a mixture of debts. Debt mixing is a mix of positions (quality) of the parties entering into an agreement so that the quality as a creditor becomes one with the quality of the debtor so that the agreement between the two parties is null and void. Mixing of debts is regulated in Article 1436 of the Civil Code to Article 1437 of the Civil Code. Debt mixing can occur because the positions of creditors and debtors become one. For example, a creditor marries a debtor, which results in a mix of debts and the agreement that previously existed is erased. Problems can arise when it relates to debts owned by creditors and debtors who eventually marry. If the creditor does not want the debt owned by the debtor to be erased even though they are both married. Even though there are clear rules emphasized that debts can be written off by law, one of which is if there is a mix-up of debts.